The biological clock gene PER1 affects the development of oral squamous cell carcinoma by altering the circadian rhythms of cell proliferation and apoptosis. (2nd September 2022) - Yin, Shilin; Zhang, Zhiwei; Tang, Hong; Yang, Kai
ABSTRACT: Circadian rhythms expressed by the biological clock gene PER1 are aberrantly altered in a variety of tumor cells, including oral squamous cell carcinoma (OSCC); however, their functions and mechanisms are unclear. Here, we found that compared with normal oral epithelial HOK cells, OSCC cells showed altered circadian rhythm characteristics of proliferation, apoptosis and PER1 expression, exhibiting abnormal changes in the 3 dimensions of mesor, amplitude and acrophase. It was further found that in OSCC cells overexpressing PER1 (OE-PER1-SCC15), the circadian rhythm characteristics of cell proliferation, apoptosis, p-AKT and p-mTOR expression were abnormally altered. After adding the AKT activator SC79 to OE-PER1-SCC15 cells, the circadian rhythm characteristics of cell proliferation, apoptosis and p-AKT and p-mTOR expression were altered in opposite ways. In vivo tumorigenic assays demonstrated that overexpression of PER1 inhibited OSCC growth. The circadian rhythm characteristics of cell proliferation and apoptosis, PER1, p-AKT and p-mTOR expression were altered similarly to those observed in vitro . Our findings demonstrate for the first time that PER1 regulates the circadian rhythm of OSCC cell proliferation and apoptosis by altering the circadian rhythm characteristics of the AKT/mTOR pathway. The results have the potential to provide a new strategy for circadian rhythm-based treatment of OSCC.